No more monsters for me! - Parish, Peggy; Simont, Marc (New York : HarperTrophy, 1987)
Minneapolis Simpkin is not allowed to have a pet, so she finds the most unusual replacement.
Keywords: Monsters -- Juvenile fiction; Fiction